Penerapan Terapi Relaksasi Otot Progresif Terhadap Kecemasan Pasien STEMI di Ruangan CVCU RSUD Prof.Aloei Saboe - Tiara Nurbaiti Nusa; Haslinda Damansyah; Susanti Monoarfa; Agusalim Dali (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Symptoms of stemi can cause patients to feel more anxious, this anxiety can be overcome pharmacologically and nonpharmacologically. However, pharmacological therapy can cause various side effects. Therefore, nonpharmacological therapies can be recommended including progressive relaxation techniques. The purpose of this study was to determine the application of progressive muscle relaxation therapy to anxiety using the HARS scale in stemi patients in the CVCU Room of Prof. Aloei Saboe Hospital. Pre-experimental research method with one group pre post test design, a sample of 4 people who met the sample criteria, the instrument used HARS (Hamilton Anxiety Rating Scale) and the data analysis used was univariate analysis. The study findings are that progressive relaxation techniques carried out by researchers for 3 days can reduce the HARS score of the first patient from a score of 11 to 4, the second patient from a score of 12 to 6, the third patient from a score of 13 to 7 and the fourth patient from a score of 12 to 6, so that progressive muscle relaxation therapy can be applied in reducing anxiety of stemi patients in the CVCU Room of Prof. Aloei Saboe Hospital. The implication of this study is that the nursing profession is expected to improve the provision of nursing interventions in carrying out the nursing care process comprehensively, namely from bio to psychosocial patients so that it can help patients overcome psychosocial problems in this case the anxiety experienced by patients.